Oxidative stress, inflammation, and markers of cardiovascular health. Issue 1 (November 2015) - Lakkur, Sindhu; Judd, Suzanne; Bostick, Roberd M.; McClellan, William; Flanders, W. Dana; Stevens, Victoria L.; Goodman, Michael
Abstract Objective To investigate associations of a oxidative balance score (OBS) with blood levels of total cholesterol, low-density lipoprotein- (LDL)-cholesterol, high-density lipoprotein- (HDL) cholesterol and triglycerides, and biomarkers of inflammation (serum C-reactive protein [CRP], albumin and venous total white blood cell [WBC] counts) among 19, 825 participants in a nationwide study. Methods Using cross-sectional data 14 dietary and lifestyle components were incorporated into the OBS and the resulting score (range 3–26) was then divided into five equal intervals. Multivariable-adjusted odds ratios (ORs) for abnormal biomarker levels and 95% confidence intervals (CIs) were calculated using logistic regression models. Results The ORs (95% CIs) comparing those in the highest relative to those in the lowest OBS equal interval categories were 0.50 (0.38–0.66) for CRP, 0.50 (0.36–0.71) for the total WBC count, and 0.75 (0.58–0.98) for LDL-cholesterol; all three p-values for trend were <0.001. The OBS-HDL-cholesterol association was statistically significantly inverse among females, but not among males. The OBS was not associated with serum albumin or triglycerides. Conclusion Our findings suggest that an OBS may be associated with some, but not all, circulating lipids/lipoproteins and biomarkers of inflammation.